Tourism crisis management : a case study on how tourism industries in Singapore and Vietnam coped with SARS. - Tran, Hai Linh. (2008)
The project aims to give a guideline for crisis management in South-East Asia. Although there have been a number of crisis in the past decade, there has been a lack of research into proper crisis management measures, particularly for the South-East Asian tourism industry.